In-depth querying of web-based medical documents: beyond single page results. (2015) - Madaan, Aastha; Chu, Wanming
The World Wide Web has become a large source of health information. The paper-based medical resources are becoming available on the web. Hence, web-based information retrieval, automatic page-adaptation and in-depth querying are gaining importance especially in the healthcare domain. To address the problems of these ever-expanding information systems over the internet, traditional information retrieval techniques are applied. This study is an attempt to highlight the challenges faced by the users in the healthcare domain for in-depth querying of web-based healthcare information resources. It compares the existing approaches for in-depth querying for segment-level searches rather than page-level searches. It proposes a web document segmentation-based 'query-by-segment tag (QBT)' query-interface. It utilises the semantic and structural relationships among the various content groups of a web document. Such a query-interface enables the user to perform in-depth querying.